Necrotizing eyelid fasciitis – Series of two cases and three eyelids - W. Adamski; M. Pankowski; C. Dzióbich (IDCases)
Necrotising eyelid inflammation, also known as necrotising fasciitis (NF) of the orbit, is a rare but severe soft tissue infection. Prompt and appropriate treatment is crucial, as delayed intervention can result in the bacteria entering the bloodstream. Typical predisposing factors for NF include skin breaks after surgery or trauma, which may be small and overlooked. NF is mainly caused by group A beta-haemolytic streptococci, with significant cases also attributed to Pseudomonas aeruginosa and Staphylococcus aureus.Symptoms include swelling, fever and pallor in the orbital region. Untreated NF can lead to serious complications such as exophthalmos of the orbit or death. The COVID-19 pandemic has led to an increase in the incidence of certain infectious diseases, including streptococcal infections, which can increase the risk of necrotising fasciitis. We present here two report cases of NF that were successfully cured by prompt and aggressive treatment.